The Political Parties Coalition Behaviour in Election: A Meta-Analysis - Subekti, Dimas; Wahid, Makmun (Universitas Indo Global Mandiri, 2023)
The formation of political party coalitions can be applied productively to patronage democracy, but this requires a broader comprehensive study and the addition of new conceptualizations. Therefore, this study aims to determine the development of research on the theme of political party coalition behavior from 2015 to 2021 indexed by Scopus. This study uses a scoping review method. The source of this research data comes from the Scopus database. The findings in this study that the coalition behavior of political parties will not be separated from the topic of voting behavior and the electoral system, this is evident in this study. The political parties in building coalitions must consider the level of electability by looking at behavior in the voters. Moreover, the electoral system will determine whether political parties need to form coalitions or not if they want to participate in electoral contestation. Furthermore, parliamentary elections and proportional representation are topics that have opportunities as novelties for future research related to this themes. Furthermore, Indonesia (southeast asia), Spain, Norway (Europa), Uruguay and Colombia (South America) have recently paid great attention to research on the political parties coalition behavior. The implications of the findings of this study are as a form of a reference for knowledge regarding the study of political parties. More than that, it is important to describe these findings because they can classify world research which so far has only been limited to individual findings.